Pemikiran Maududi tentang Bank Syariah - Faozan, Akhmad (International Conference of Moslem Society, 2016)
One thinker who care about the Muslims’economy is Maududi. Banking problems is one issue that can not escape his attention. It offers a model or banking system in accordance with Islamic principles. According to him, the model or the system can deliver a fair banking concept. Maududi thinking about islamic bank consists of two things, namely the elimination of interest system and profit sharing system in its operations. Although the system was abolished interest of Islamic banking, he remains optimistic that people will still be saving money in the bank. According to Maududi, in the profit sharing system customers will no longer earn interest and instead they will get something in the term is the result. Profit received from the parties developing the bank customer money will be distribute between the bank and the customer in accordance with the agreement. Meanwhile, the background factors Maududi thinking about his obsession about Islamic bank is to stand an Islamic state that would load the Islamic economic system as well.